Incidence and predictors of left atrial appendage thrombus on transoesophageal echocardiography before elective cardioversion. (14th October 2021) - Wegner, F; Radke, R; Ellermann, C; Wolfes, J; Fischer, A J; Baumgartner, H; Eckardt, L; Diller, G P; Orwat, S
Abstract: Introduction: Guidelines recommend transoesophageal echocardiography (TOE) before cardioversion in thrombogenic arrhythmias when the requirement of ≥3 weeks of anticoagulation is not met. Current data to support this approach, especially with direct oral anticoagulants (DOAC), are scarce. Methods: We analysed consecutive elective pre-cardioversion TOE in a high-volume electrophysiology centre for the occurrence of LAA thrombi or reduced LAA flow velocity. Possible predictors were recorded and compared in a multivariate logistic regression analysis. Results: Consecutive pre-cardioversion TOE in 512 patients (148 female, median age 69 years) were included. In all patients, indication for TOE was either intake of anticoagulation <3 weeks before cardioversion or uncertain adherence to the prescribed anticoagulation regimen. Of the 512 TOE, 19 (3.7%) depicted a LAA thrombus. An additional 41 patients (8.0%) showed either a reduced LAA flow velocity (≤20cm/s), LAA sludge, or both (see figure). In a multivariate logistic regression analysis, QRS width on admission 12-lead ECG emerged as a possible predictor of LAA thrombus and reduced LAA flow (p=0.008). Noteworthy, a high CHA2DS2-VaSc-Score was not associated with an increased risk of reduced LAA emptying velocity and LAA thrombi were even found in patients with a CHA2DS2-VaSc-Score of 0 (n=1) and 1 (n=1). Conclusion: The presence of LAA thrombus before an elective cardioversion is a rare event in the age of direct oral anticoagulants. However, LAA thrombi occurred even in supposed low-risk individuals according to the CHA2DS2-VaSc score. QRS width may aid in identifying patients at a high risk of a reduced LAA flow velocity. Funding Acknowledgement: Type of funding sources: None.